A Community Partnership Approach to Digital Literacy Training for Older Adults Between Public Libraries and Seniors’ Organizations - Elgamal, Raghad; La Rose, Tara; Detlor, Brian; Julien, Heidi; Serenko, Alexander (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This exploratory case study investigates the role of a partnership approach in Canada between two public library systems, a volunteer seniors’ organization, and a seniors’ centre as a means of enhancing digital literacy among older adults (65+). The inquiry draws upon individual semi-structured interviews with administrators, instructors, voluntary facilitators, and older adult learners who participated in the training. Findings highlight the importance of incorporating opportunities for socialization and relationship-building into training sessions. Implications and considerations for future research in the realm of community partnerships and digital literacy for older adults are discussed. The study emphasizes the value and challenges of partnerships in enhancing digital literacy among older adults through social support and tailored instruction.